The Utility of Real-Time Quantitative Polymerase Chain Reaction Genotype Detection in the Diagnosis of Urinary Tract Infections in Children. (September 2017) - Felt, Jon R.; Yurkovich, Chelsey; Garshott, Danielle M.; Kamat, Deepak; Farooqi, Ahmad; Fribley, Andrew M.; Callaghan, Michael U.; Hebert, Katherine
Urinary tract infections (UTIs) are the most common serious bacterial infection in children with significant morbidity with delayed diagnosis. Polymerase chain reaction (PCR) is very accurate in detecting bacteria and widely available, but has never been evaluated to detect UTIs in children. To assess the utility of PCR as a rapid diagnostic tool, we conducted a prospective cohort study of 193 urine samples from children younger than 36 months undergoing evaluation for UTI in the emergency department over a 10-month period. A quantification cycle (Cq) threshold of 26.15 identified all Escherichia coli positive samples with sensitivity and specificity of 100% and 99.5%, respectively (95% CI = 71.5%-100% and 97.9%-99.5%, respectively). A Cq threshold of 19.03 identified E coli infections >100 000 colony forming units/mL with sensitivity and specificity of 100% (95% CI = 72.2%-100% and 98.6%-100%, respectively). PCR is very accurate in diagnosing E coli UTIs in young children and could be useful as a rapid diagnostic tool.